An introduction to engine testing and development - Atkins, Richard D., 1940- (Society of Automotive Engineers. Electronic publications., 2009)
With useful information for graduate students, new test technicians, and established engineers, this book explains the test process - from setting up a dynamometer test facility to testing for performance and durability. Combustion analysis and emissions, and new test trends are also covered.